Historical and Administrative Analysis of Bharath Heavy Electricals Limited (Bhel) at Ranipet – A Study - Babu, Prakash K; Thiripurasundari, P (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
This study examines the historical development and administrative structure of Bharat Heavy Electricals Limited (BHEL) in Ranipet. Established as part of India’s post-independence industrialization policy, the Ranipet unit played a significant role in strengthening the country’s heavy electrical equipment manufacturing sector. The research traces the origin and growth of BHEL in Ranipet, highlighting its contribution to regional industrial development, employment generation, and technological advancement. The study also analyzes the administrative set-up of the organization, including its hierarchical structure, functional divisions, decision-making processes, and managerial practices. By examining primary and secondary sources, the research evaluates how administrative efficiency contributed to productivity and organizational growth. The study concludes that the historical evolution and structured administration of BHEL Ranipet significantly influenced both industrial progress and socio-economic development in the region.
Keywords: BHEL Ranipet; Administrative Structure; Heavy Electricals Industry; Industrial Development